Implantation of a Trifocal Intraocular Lens in High Myopic Eyes with Nasal-Inferior Staphyloma - Alfonso-Bartolozzi B (Dove Medical Press, 2020)
Belén Alfonso-Bartolozzi,1 Eva Villota,1 Álvaro Fernández-Vega-González,1 Luis Fernández-Vega-Cueto,1 Álvaro Fernández-Vega,1 José F Alfonso1,2 1Fernández-Vega Ophthalmological Institute, Oviedo, Spain; 2Surgery Department, School of Medicine, University of Oviedo, Oviedo, SpainCorrespondence: José F AlfonsoInstituto Oftalmológico Fernández-Vega, Avda. Dres. Fernández-Vega 114, Oviedo, 33012 SpainTel +34 985 245533Fax +34 985 233288Email j.alfonso@fernandez-vega.comPurpose: To assess visual outcomes in high myopic eyes with nasal-inferior staphyloma implanted with a pseudophakic trifocal intraocular lens (IOL).Methods: We retrospectively analyzed the visual outcomes of 50 eyes of 45 patients who had cataract surgery after AT LISA trifocal IOL implantation. Twenty-five eyes diagnosed with posterior staphyloma (nasal-inferior, type IV and V), and 25 eyes as long eyes. Uncorrected distance visual acuity (UDVA) and corrected distance visual acuity (CDVA) values were used to assess the efficacy and safety of the surgery. Refraction and defocus curves were also evaluated at 6 months.Results: No intra- or post-operative problems occurred during the 6 months of follow-up. After the surgery, the mean Snellen decimal UDVA ranged from 0.50 to 1.00, and CDVA from 0.60 to 1.00 for both groups. CDVA was 0.91 and 0.74 for the long eye and nasal-inferior staphyloma groups, respectively. Efficacy and safety indexes were 1.22 and 1.32 for the long eye, and 1.26 and 1.43 for the nasal-inferior staphyloma group, respectively. All eyes of both groups showed a postoperative spherical equivalent within ± 1.00D. The long eye group showed the highest percentage of spherical equivalent between − 0.13D and +0.13D (56%) and the nasal-inferior staphyloma group was between − 0.51D and − 0.14D (40%).Conclusion: The outcomes of the present study show that a trifocal IOL provides good visual acuity in high myopic eyes, being worse for nasal-inferior staphyloma eyes. The degree of tilt of the macular plane is related with the expected visual acuity.Keywords: high myopia, multifocal intraocular lens, phacoemulsification, staphyloma